Kajian etnoperubatan, analisis fitokimia dan aktiviti biologi tumbuh-tumbuhan antidiabetik terpilih yang digunakan oleh masyarakat orang asli di Gua Musang, Kelantan - Hamzah, Nurraihana (2015)
Diabetes is one of the chronic diseases affecting worldwide population. Presently, there is a growing interest in herbal remedies for diabetic patient. Therefore, an investigation based on ethnomedicine is required in determined alternative approaches to treat diabetics, such as herbal. The main objective of this study was to document ethnomedical of medicinal plants used by aborigines in Gua Musang, Kelantan. The phytochemical, phytonutrient and biological activities of selected plants were screened. Ethnomedical information was collected by interviewing the aboriginal households (house-to-house interviews) and traditional healers in the village. The antidiabetic potential of aqueous extract of selected medicinal plants was determined using α-glucosidase and α-amylase inhibition assay. Phytochemical and phytonutrient were quantitatively determined using standard procedure and antioxidant activities were determined using 2,2’-azinobis(3- ethylbenzothiazoline-6-sulphonic) asid (ABTS), 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and ferric reducing/antioksidan power (FRAP) assays. The ethnomedicinal data revealed that 46 plant species were used in treating various types of health problems, from common diseases such as muscle aches and fever to chronic diseases such as diabetes, hypertension and malaria. From the species recorded, three plants used to treat diabetes is Albizia myriophylla, Oxalis barrelieri and Tacca cristata. Therefore, those plants were term as antidiabetic plants in this study. All extracts were found to have significant antidiabetic activities. A. myriophylla extract showed the highest inhibitory activity against α-amylase in which IC50 15.05 μg/ml, while O. barrelieri showed the highest inhibitory activity against α-glucosidase in which IC50 52.40 μg/ml. O. barrelieri showed the highest phenolic content (64.30 ± 1.50 mg GAE/g), flavonoid content (19.29 ± 2.90 mg CE/g), tannin (42.59 ± 10.23 mg TAE/g), alkaloid (3.27 ± 0.33%), fat (1.47 ± 0.60%) and protein (10.61 ± 0.72%) while T. cristata showed the highest content of saponin (7.17 ± 1.15), ash (10.25 ± 0.15%), carbohydrate (53.51 ± 0.94%) and gross energy (240.93 ± 1.74 kcal/100g). Mineral analysis indicates higher concentrations of magnesium, sodium, calcium, mangan, ferum and zinc in T. cristata while higher concentrations of potassium and phosphorus in O. barrelieri. O. barrelieri extract also had the highest antioxidant acivities in ABTS, DPPH and FRAP assays in which 205.95 μmol Trolox/g, 110.41 μmol Trolox/g and 220.93 μmol Trolox/g were obtained, respectively. Further, the most potent extract which is O. barrelieri was subjected to functional beverage development for antidiabetic study in rat model. The results revealed that the O. barrelieri juice showed blood glucose lowering effects in STZ-induced diabetic rats. In conclusion, A. myriophylla, O. barrelieri and T. cristata were found to possess significant in vitro antidiabetic and antioxidant activities. Besides that, O. barrelieri juice showed antidiabetic potential in rat animal models.